Use of pelvic ultrasound to monitor ovarian and uterine maturity in childhood onset anorexia nervosa. Issue 3 (September 1994) - Lai, K Y; de Bruyn, R; Lask, B; Bryant-Waugh, R; Hankins, M
Abstract : This study reports the use of pelvic ultrasound scanning in childhood onset anorexia nervosa. The aim was to determine the weight and weight for height ratio (wt/ht) that would correspond with ovarian and uterine maturity and therefore offer the optimal opportunity for the start or resumption of menstruation. On initial assessment, all children had mean weight, wt/ht, ovarian and uterine volumes significantly below expected. At follow up, half the children had started or resumed menstruation. When compared with those who had persisting amenorrhoea, the recovered children had a significantly higher mean weight (48.4 kg v 43.8 kg), mean wt/ht (96.5% v 87.5%), mean ovarian volume (6.2 ml v 4.9 ml), and mean uterine volume (14.6 ml v 10.8 ml). The study indicates that conventional target weight and wt/ht in anorexia nervosa may be too low to ensure ovarian and uterine maturity, and that pelvic ultrasound, which is well tolerated by this group of children, is a useful addition to their management.